Reconsideration of the Late Fourth and Third Millennium B.C. in the Arabian Gulf, with Special Reference to the United Arab Emirates - al-Tikriti, W. Y. (1982)
Ph.D. Dissertation; Wal?d Y?s?n al-Tikr?t?.